Analisis Faktor-Faktor yang Memengaruhi Nasabah Non-Muslim dalam Menggunakan Jasa Bank Syariah di DKI Jakarta - Fithri Tyas Hapsari; Irfan Syauqi Beik (Department of Islamic Economics, IPB University, 2014)
Islamic banking industry in Indonesia experienced significant growth and development, despite its market share is still small, i.e around 4.9%. Islamic bank is an intermediary institution based on sharia, which serve both muslim and non-muslim. This study analyzes the factors that affect non-Muslim customers in using the services of Islamic banks in Jakarta. Respondents used in this study consist of 50 non-Muslim customers of Islamic banks and 50 non-Muslim customers of conventional banks. The method used is the logistic regression method. Descriptive analysis methods is used to see the trend of non-Muslim customers towards Islamic banks. Factors that are significantly affecting non-Muslim customers in using the services of Islamic banks in Jakarta are the location factor with an odds ratio value of 1.450, factor of administrative advantages with an odds ratio value of 6.790, and religious stimulant factor with an odds ratio value of 2.679.